Glacier Trail - c.1550 Reconstruction - Sarah Kennedy; Skúli Gunnarsson; Catherine Anne Cassidy; Iain Oliver; Alan Miller (Zenodo, 2021)
In the year 1550, the monastery of Skriðuklaustur owned farms in the East-fjords in Iceland. Some were bought while others were donated to save the souls of relatives that passed away. One of the monastery's estates was in the Southeast of Iceland, on the other side of the great Vatnajökull glacier. To get there from Skriðuklaustur you had to travel for more than 100 kilometers and cross the glacier. This estate was one of the most important for the monastery because it was a fishing site for the Icelandic cod. The monastery sent their men there to fish for part of the year, and the catch was dried for storage. The men brought back some of the fish to the Fljotsdalur valley where it provided important nutrition for the patients and people of the cloister. However, the majority of the catch was probably exported to Europe with Hanseatic ships as a financial resource for the monastery. This reconstruction takes you along the glacier trail from Skriðuklaustur to Hálsahöfn and Borgarhofn, the route that the fishermen travelled centuries ago. Along the path you’ll see farms, a stave church, longhouses, the peak of the glacial, and the fishing site. In the 16th century, the Vatnajökull glacier was not the same hindrance that it is today, but one can wonder if climate change will make this area passable again. A Collaborative project between Open Virtual Worlds , a research team within the School of Computer Science, University of St Andrews and the Gunnar Gunnarsson Institute. Funded by the EU Northern Periphery and Arctic Programme 2014-2020 through the “Connected Culture and Natural Heritage in a Northern Environment” ( CINE ) project.